Hartz IV: The German ?Word of the Year 2004? and the Country?s Hope to overcome its Problem of Unemployment - Tim Lohse (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
When the centre-left government came into power in Germany in 1998, a core promise of the new Chancellor, Schroeder, was to reduce the lack of jobs and to increase welfare. Facing persistently increasing unemployment rates from then on, the government finally launched ?Hartz IV? in 2004; the largest social reform project in the history of the Federal Republic. This reform, that took effect at the beginning of 2005, aims to increase employment in Europe?s biggest but slowest growing economy, whilst avoiding the financial collapse of its social systems. Its main aim is to strengthen individual responsibility whilst lowering transfers for those unemployed individuals that are capable of work. Therefore, it is also the most disputed reform of the German social welfare system. By characterising effects and defects of the German welfare system, we identify some of the most important obstacles facing higher employment. We provide an outline of the government?s endeavours to handle the problem of unemployment and of the main changes in the country?s laws of social contributions. Particular focus is given to the newly established unemployment benefit II and to the ?reasonableness? of work, which reflects a new social valuation of labour. To conclude, potential welfare and employment effects under the new sys-tem are discussed.
Keywords: J64; I38; 330; Welfare; Unemployment; Poverty